2017
DOI: 10.2147/tcrm.s137144
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Weber effect in contemporary pharmacovigilance of oncology drugs

Abstract: BackgroundNumerous reporting biases have been known to affect spontaneous reporting databases. The Weber effect, which constitutes a peak in adverse event (AE) reporting of a drug at the end of second year after regulatory approval followed by a continuous decline thereafter, has been considered an important bias for a long time. The existence of this bias in AE reporting of oncology drugs remains an underevaluated area, prompting a targeted examination.MethodsThe US Food and Drug Administration (USFDA) Advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…6 A review of the literature indicates that this effect has been sought after on several occasions with varying results, thereby leading some authors to question the reproducibility of the Weber effect. [7][8][9][10][11] It has also been observed that most of the evaluations conducted on Therefore, the current study was designed to evaluate the validity of the Weber effect in the context of medicines used in a specialty care setting on a more granular level, utilising sales volume data as a proxy for patient exposure. The study also evaluated the reporting trend differences among solicited and unsolicited safety reports, as well as the type of information reported via these systems i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 A review of the literature indicates that this effect has been sought after on several occasions with varying results, thereby leading some authors to question the reproducibility of the Weber effect. [7][8][9][10][11] It has also been observed that most of the evaluations conducted on Therefore, the current study was designed to evaluate the validity of the Weber effect in the context of medicines used in a specialty care setting on a more granular level, utilising sales volume data as a proxy for patient exposure. The study also evaluated the reporting trend differences among solicited and unsolicited safety reports, as well as the type of information reported via these systems i.e.…”
mentioning
confidence: 99%
“…The authors evaluated AR reports from the FAERS database,and adjusted the number of reports to the number of dispensed prescriptions from US outpatient retail pharmacies, as a proxy for drug exposure 9. Similarly, analyses conducted by Arora et al7 and Hoffman et al20 studied recently approved drugs and utilised data from FAERS.There was no observation of a second-year peak nor of a subsequent fall in the volume of AR reports. One important observation evident from the review of studies conducted with drugs used in a specialty care setting is that whilst Weber 5 attributed the changing trends in AR reporting to drug exposure and familiarity of the drug, the studies thus far have primarily relied upon the absolute number of ARs from the source system (usually the Adverse Event Reporting System for the USA, which was the predecessor of FAERS).…”
mentioning
confidence: 99%
“…The result of which could underestimate the effect IAC had on the incidence of hemolysis. Finally, the Weber effect, which describes the effect where spontaneous reporting of adverse events peaks at the end of the second year after regulatory approval and declines steadily thereafter, is a potential confounder for reporting database studies . However, considering that IVIG has been around for decades, the clear directional shift in hemolysis reporting rates following implementation of IAC in 2016 is unlikely to be attributable to the Weber effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis focused on severe events where underreporting is less likely, as practitioners continue to report serious adverse drug reactions after the initial years of marketing [24]. It is also worth noting that recent research has challenged the existence of a Weber effect, originally described in 1984 [26,27].…”
Section: Discussionmentioning
confidence: 99%